Інноваційні підходи режимного експрес-аналізу до системи контролю зсувних масивів - Бурачек, В.Г.; Олінович, А.С.; Кривоберець, С.В. (Екологічна безпека та природокористування, 2012)
Discussed innovative approaches at the express analysis of landslide monitoring system. Analysis of geodetic techniques and tools that are used for monitoring the provisions of points on the Earth's surface.